Technological Tools Integration in the Academic Training of Translators and Interpreters: A Study on the Teachers' Perspectives - Rami BOUOUDEN; Saida KOHIL; Yasmine DAOUD (Langues & Cultures)
Incorporating technology in academic translation and interpreting training programs has become crucial, especially in a job market that requires mastering various tools. This paper looks into the reality and importance of technological tools in training translators and interpreters at the Institute of Translation, Algiers 2 University, from the teachers' perspective. It was conducted through a mixed-methods approach, using a questionnaire to collect qualitative and quantitative data from 38 teachers. The findings revealed that participants had a favorable attitude toward technological tools with varying degrees of utilization during training. While most showed general technological competency, the lack of specialized training and limited access to essential equipment in the institute surfaced as critical hurdles. To resolve these inconsistencies, translation institutes in Algeria must provide the required equipment and extensive technology training for teachers and work on aligning training with the novelties of the job market.